Analisis Frekuensi Resonasi Jembatan Bantar III Bantul Yogyakarta Terhadap Kejadian Gempabumi Yogyakarta - Meilan Demulawa; Dewa Gede Eka Setiawan; Muhammad Yunus; Rusni R Rifai (Peneliti.net, 2022)
A vibration resonance studies were performed at Bantar III Bridge Kali Progo Sedayu Sub-district of Bantul. The study aims to determine the natural frequency of the bridge and compare it with the frequency of earthquakes to determine the possibility of resonance. Spectral analysis of the earthquake and the bridge using the FFT to obtain the dominant frequency of the bridge and the frequency of earthquakes. The natural frequency of the bridge obtained about 3,5 Hz – 5Hz. This is apropriate with the analytical calculation based on the construction of the bridge that showed the natural frequency about 3.51 Hz - 5.18 Hz. The frequency survace wave of the Yogyakarta earthquake which took place within the periode 2009 – 2010 is 1,1 Hz – 3,3 Hz. Comparison of natural frequency experimentally and the frequency of earthquakes indicated very small possibility of resonance amplification occured in the Bantar III bridge Kali Progo Yogyakarta.